2018
DOI: 10.3390/cancers10040120
|View full text |Cite
|
Sign up to set email alerts
|

Perspective: Contribution of Epstein–Barr virus (EBV) Reactivation to the Carcinogenicity of Nasopharyngeal Cancer Cells

Abstract: Nasopharyngeal carcinoma (NPC) is a squamous cell carcinoma derived from the epithelium of the post-nasal cavity, with a unique geographic and ethnic distribution. Epstein–Barr virus (EBV) is an etiological agent of NPC, but how it contributes to carcinogenesis is not completely clear. Although it is thought that EBV latency participates in the development of NPC, increasing evidence reveals that the lytic cycle also plays an important role in the carcinogenic process. In this review, we summarize our recent s… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

0
15
0

Year Published

2018
2018
2022
2022

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 17 publications
(15 citation statements)
references
References 30 publications
0
15
0
Order By: Relevance
“…It has been reported that PI3K and MAPK pathways play an important role in recurrent chemical reactivations of EBV, which promotes genome instability and enhances tumor progression [17]. Given that EBV reactivation appears to play an important role in the pathogenesis of EBV-associated diseases [15,16], we think smoking-induced EBV reactivation could contribution to the pathogenesis of EBV-associated diseases. The large variation in oral EBV loads among individuals, from undetectable levels (<5 copies in this study) to several billion copies/mL, was consistent with previous findings of virus shedding dynamics in healthy carriers [32].…”
Section: Discussionmentioning
confidence: 87%
See 1 more Smart Citation
“…It has been reported that PI3K and MAPK pathways play an important role in recurrent chemical reactivations of EBV, which promotes genome instability and enhances tumor progression [17]. Given that EBV reactivation appears to play an important role in the pathogenesis of EBV-associated diseases [15,16], we think smoking-induced EBV reactivation could contribution to the pathogenesis of EBV-associated diseases. The large variation in oral EBV loads among individuals, from undetectable levels (<5 copies in this study) to several billion copies/mL, was consistent with previous findings of virus shedding dynamics in healthy carriers [32].…”
Section: Discussionmentioning
confidence: 87%
“…All of these findings consistently suggest that individuals with high lytic EBV antibody levels have greatly increased malignancy risks, revealing that EBV reactivation could be present prior to clinical onset. Given that EBV reactivation appears to play an important role in the pathogenesis of EBV-associated disease [11][12][13][14][15][16][17], determining the inducing factors would be helpful in the primary prevention of EBV reactivation, even to the EBV-associated diseases. Several agents, such as tetradecanoylphorbol acetate, phorbol ester, calcium ionophores, and some extracts of food containing mycotoxin aflatoxin B1, Cantonese-style salted fish, Chinese herbs have been reported to contribute to EBV reactivation [18][19][20][21][22][23][24][25].…”
mentioning
confidence: 99%
“…Epstein‐Barr virus (EBV) infection is a well‐established risk factor for undifferentiated NPC, which accounts for more than 90% of the total cases in endemic areas . Elevated serological antibodies against EBV can be observed several years before an NPC diagnosis . However, EBV is a ubiquitous herpesvirus that infects more than 90% of individuals worldwide, yet only a small fraction develop NPC; this indicates that other risk factors are also involved in NPC etiology …”
Section: Introductionmentioning
confidence: 99%
“…3 Elevated serological antibodies against EBV can be observed several years before an NPC diagnosis. [4][5][6] However, EBV is a ubiquitous herpesvirus that infects more than 90% of individuals worldwide, yet only a small fraction develop NPC; this indicates that other risk factors are also involved in NPC etiology. [7][8][9] Herbal substances in teas or soups, traditional dietary staples in southern China, may be linked to the development of NPC, perhaps because of their ability to reactivate EBV or through a direct proliferative effect on EBV-transformed cells.…”
Section: Introductionmentioning
confidence: 99%
“…44,45 In NPC, recurrent induction of EBV lytic cycle contributes more profoundly to NPC carcinogenesis. 46 Taken together, our observations suggest that targeting lytic proteins combined with latent proteins could be more efficient for autologous CTL infusion or vaccination strategies. In the last few years, chimeric antigen receptor (CAR) T-cell therapy has shown promising efficacy in the treatment of B lymphoma.…”
Section: Discussionmentioning
confidence: 60%